Emission characteristics of fine particulate matter from ultra-low emission power plants. (December 2019) - Chen, Xiaojia; Liu, Qizhen; Yuan, Chao; Sheng, Tao; Zhang, Xufeng; Han, Deming; Xu, Zhefeng; Huang, Xiqian; Liao, Haoxiang; Jiang, Yilun; Dong, Wei; Fu, Qingyan; et al.
Abstract: As one of the highest energy consuming and polluting industries, the power generation industry is an important source of particulate matter emissions. Recently, implementation of ultra-low emission technology has changed the emission characteristic of fine particulate matter (PM2.5 ). In this study, PM2.5 emitted from four typical power plants in China was sampled using a dilution channel sampling system, and analyzed for elements, water-soluble ions and carbonaceous fractions. The results showed that PM2.5 concentrations emitted from the four power plants were 0.78 ± 0.16, 0.63 ± 0.09, 0.29 ± 0.07 and 0.28 ± 0.01 mg m −3, respectively. Emission factors were 0.004–0.005 g/kg coal, nearly 1–2 orders of magnitude lower than those reported in previous studies. The highest proportions of PM2.5 consisted of organic carbon (OC), SO4 2−, elemental carbon (EC), NH4 +, Al and Cl − . Coefficients of divergence (CDs) were in the ranges 0.22–0.41 (for an individual plant), 0.43–0.69 (among different plants), and 0.60–0.99 (in previous studies). The results indicated that the source profiles of each tested power plant were relatively similar, but differed from those in previous studies. Enrichment factors showed elevated Se and Hg, in accordance with the source markers Se and As. Comparing source profiles with previous studies, the proportion of OC, EC and NH4 + were higher, while the proportion of Al in PM2.5 were relatively lower. The OC/EC ratio became concentrated at ∼5. Results from this study can be used for source apportionment and emission inventory calculations after implementation of ultra-low emission technologies. Graphical abstract: Image 1 Highlights: PM2.5 concentrations from tested ultra-low emission (ULE) power plants were <1 mg m −3 . Emission factors were 1-2 orders of magnitude lower than reported in previous studies. PM2.5 was mostly organic carbon, SO4 2−, elemental carbon, NH4 +, Al, and Cl − . Carbon and NH4 + increased; geological elements decreased after the ULE-retrofitted. Abstract : Capsule: The proportion of organic carbon and NH4 + increases and the proportion of geological material decreases in PM2.5 from ultra-low emission power plants.